Head (Canadian Medical Education Journal, 2019)
To fully understand something you must break it down to its simplest form. This is especially true for medicine. In order to appreciate challenging concepts, you need to have a basic comprehension of all components. I completed this piece as a medical student where I was confronted with new information that relied on my prior learning to build a bigger picture. This piece was constructed by adding small strips of paper folded in distinct patterns that as a collection form an overall image.